Subdural Effusion and Infantile Neuronal Ceroid Lipofuscinosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
During the course of an ongoing NIH clinical study evaluating the benefit of cysteamine and N-acetylcysteine in 9 patients with infantile neuronal ceroid lipofuscinosis (INCL), 4 were found to have subdural fluid collections without mass effect.